2014
DOI: 10.1159/000364878
|View full text |Cite
|
Sign up to set email alerts
|

Similar Psychopathological Profiles in Female and Male Cushing's Disease Patients after Treatment but Differences in the Pathogenesis of Symptoms

Abstract: Background: Female Cushing's disease (CD) patients with active disease present more frequently with depression compared to their male co-sufferers. This study investigated whether the gender difference prevails after remission and whether gender-specific factors contributing to mental health exist. Methods: 72biochemically cured CD patients (11 male, mean age 45.9 ± 13.7 years) who underwent transsphenoidal tumour removal filled out the Symptom Checklist-90-Revised inventory on average 42.1 ± 32.9 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 32 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…One study reported more macroadenomas, with higher invasion and apoplexy rate (11), whereas another study reported equal percentages of macroadenomas in males and females (12). No differences were found in quality of life between males and females on multiple validated questionnaires (CushingQoL, EQ-VAS, and SCL-90-R) (8, 11, 17). Table 1 summarizes the reported literature regarding sex differences (also reported as gender differences) in Cushing's syndrome (818).…”
Section: Introductionmentioning
confidence: 85%
“…One study reported more macroadenomas, with higher invasion and apoplexy rate (11), whereas another study reported equal percentages of macroadenomas in males and females (12). No differences were found in quality of life between males and females on multiple validated questionnaires (CushingQoL, EQ-VAS, and SCL-90-R) (8, 11, 17). Table 1 summarizes the reported literature regarding sex differences (also reported as gender differences) in Cushing's syndrome (818).…”
Section: Introductionmentioning
confidence: 85%